SYNTACTICAL ANALYSIS OF ONOMATOPOIC WORDS IN MODERN ENGLISH - Zarifa Ochilova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the syntactic connections of onomatopoic words in modern English. In modern English, onomatopoeic words communicate in a sentence through nuclear predicative, subordinative, and coordinative connections.